2021
DOI: 10.3389/fpls.2020.578812
|View full text |Cite
|
Sign up to set email alerts
|

nifH Gene Sequencing Reveals the Effects of Successive Monoculture on the Soil Diazotrophic Microbial Community in Casuarina equisetifolia Plantations

Abstract: The growth and productivity of Casuarina equisetifolia is negatively impacted by planting sickness under long-term monoculture regimes. In this study, Illumina MiSeq sequencing targeting nifH genes was used to assess variations in the rhizospheric soil diazotrophic community under long-term monoculture rotations. Principal component analysis and unweighted pair-group method with arithmetic means (UPGMA) clustering demonstrated distinct differences in diazotrophic community structure between uncultivated soil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This process serves as a major source of N, accounting for about 97% into the environment [25]. Recently, a molecular marker of nifH gene family which encodes for the nitrogenase reductase subunit has been used to analyze diazotrophic community structures [25,26]. N2 fixer is sensitive to soil amendment practices.…”
Section: Introductionmentioning
confidence: 99%
“…This process serves as a major source of N, accounting for about 97% into the environment [25]. Recently, a molecular marker of nifH gene family which encodes for the nitrogenase reductase subunit has been used to analyze diazotrophic community structures [25,26]. N2 fixer is sensitive to soil amendment practices.…”
Section: Introductionmentioning
confidence: 99%
“…They were also found in the rhizospheric soils of plants grown on Ebinur Lake Wetlands, but not in the paddy fields (Davis et al, 2011;Wang et al, 2020;Zhang et al, 2021). In coastal alkaline soil, Ectothiorhodospira attached to anoxygenic purple sulfur bacteria and played a role in the process of N fixation (Tourova et al, 2014;Zhou et al, 2021). We observed that the community structure of diazotrophic microbes in the tested rhizospheric soil samples were significantly affected by the types of halophytes, and as indicated by the high throughput sequencing analysis, Ectothiorhodospira was significantly different in the diazotrophic microbial community of halophyte rhizosphere (Table 2; Figures 5A-C).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that there was an increase in the number of pathogenic microorganisms in rhizosphere soil, and a concurrent decrease in the number of probiotic bacteria. Furthermore, continuous planting results in a reduction in the number of microorganisms involved in the nutrient cycle of C. equisetifolia in rhizosphere soil, a decrease in the expression levels of relevant genes, and a decline in soil available nutrients, ultimately leading to reduced nutrient absorption and accumulation in C. equisetifolia [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%